Perceived Organizational Support and Employee Performance: A Moderating Role of Organizational Justice during COVID-19 - Taha Shabbir; Kehkashan Naz; Sunil Dutt Trivedi (International Journal of Educational Administration, Management, and Leadership, 2021)
The employee’s in-role and extra-role performance has badly effected due to prevalence of COVID-19. The aim of the study is to examine the relationship of perceived organizational support and employee performance. The role of organizational justice is examined as a moderator. A sample of 222 bank employees was selected on convenience basis. The responses were recorded through closed ended questionnaires. The responses were analyzed through Partial Least Square Structural Equation Modeling Method. In times of COVID-19 the perceived organizational support has an antidotal effect on employee’s performance. At the same time the organizational justice has a significant role in the relationship of perceived organizational support and employee performance. The managers interested to have good performance of employees have to ensure organizational support along with justice in organizational practices. The perceived organizational support and justice induce trust among employees and compel them to work with diligence. The organizational justice has greater contributions towards performance. The study has examined the non-linear relationship between perceived organizational support and employees’ performance in bank employees in the context of COVID-19. In such times the people expect increased need for organizational support to fight out the challenges